Legal default rules: the case of wrongful discharge laws - W. Bentley MacLeod; Voraprapa Nakavachara (Institute for the Study of Labor (IZA), 2006)
One of the most vexing public policy issues is the extent to which governments should intervene into private contractual relationships. The purpose of this paper is to explore both theoretically and empirically the extent to which such interventions may enhance efficiency. In the case of employment law, economists have traditionally taken the view that intervention, such as protection against wrongful discharge, simply undoes the original intent of the parties to the agreement. We find that both the good faith and the implied contract exceptions to employment at will may enhance employment in occupations characterized by high levels of investment. These results suggest that under the appropriate conditions courts may enhance the operation of a competitive market by setting appropriate default remedies for breach of contract.
Keywords: J11; J21; J31; J61; K12; K31; 330; employment law; wrongful discharge; private contracts; default rules